Stratigraphy and paleomagnetism of a 2.9-km composite lava section in Eyjafjrdur, Northern Iceland: a reconnaissance study (Dataset) ... - Kristjansson, Leo; Agust Gudmundsson; BjRnS. Hardarson (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Stratigraphy and paleomagnetism of a 2.9-km composite lava section in Eyjafjrdur, Northern Iceland: a reconnaissance study ...